Analysis of Determinants of Private College Selection by Students - Hanum Putri Pramesti; Arif Hartono (International Journal of Education, Vocational and Social Science, 2024)
Education is a way to improve the standard of living, and improve the quality of life of the community. One of them is the quality of education which plays an important role in an institution of Higher Education which aims to ensure that the institution has quality attractiveness. This study aims to examine the influence of prestige, the influence of facilities, the influence of attractiveness, the influence of the media, and the influence of brands on students' decisions in choosing universities. The study was conducted on students in the 1st (one) semester of the 2023 batch. The research method used in this study is quantitative. The data collection technique was by distributing an online questionnaire to 155 respondents using Google Form. The data analysis method uses descriptive analysis, factor analysis processed using SPSS software, and Multiple Linear Regression analysis processed using SPSS software. The results of this study show that prestige analysis, facility analysis, attraction analysis, social media analysis, and brand analysis have a positive effect on student decisions.